2018
DOI: 10.1002/qj.3242
|View full text |Cite
|
Sign up to set email alerts
|

A probabilistic verification score for contours: Methodology and application to Arctic ice‐edge forecasts

Abstract: We introduce a verification score for probabilistic forecasts of contours – the Spatial Probability Score (SPS). Defined as the spatial integral of local (Half) Brier Scores, the SPS can be considered the spatial analogue of the Continuous Ranked Probability Score (CRPS). Applying the SPS to idealized ensemble forecasts of the Arctic sea‐ice edge in a global coupled climate model, we demonstrate that the metric responds in a meaningful way to ensemble size, spread, and bias. When applied to individual forecast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(60 citation statements)
references
References 28 publications
1
59
0
Order By: Relevance
“…In this study, the position of the sea ice edge in the ECMWF SEAS5 retrospective forecasts has been evaluated using various verification scores. The SPS is correlated to the length of the ice edge (Goessling & Jung, ; Zampieri et al, ) and is therefore not suitable for analyzing the seasonal variation of the forecast errors without normalization. The SPS length and the MHD are more relevant verification scores for comparing the forecast errors during different seasons.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, the position of the sea ice edge in the ECMWF SEAS5 retrospective forecasts has been evaluated using various verification scores. The SPS is correlated to the length of the ice edge (Goessling & Jung, ; Zampieri et al, ) and is therefore not suitable for analyzing the seasonal variation of the forecast errors without normalization. The SPS length and the MHD are more relevant verification scores for comparing the forecast errors during different seasons.…”
Section: Discussionmentioning
confidence: 99%
“…The IIEE length has been calculated using binary values from the 50% threshold for the SIP (1 if the SIP is higher than 50% and 0 otherwise). We have found that the IIEE length and the SPS length are very well correlated (Pearson coefficient of 0.97) and that the IIEE length is about 44% larger than the SPS length , which is consistent with the findings from Goessling and Jung ().…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations